Genotoxic Evaluation in Tadpoles Associated with Agriculture in the Central Cerrado, Brazil - Borges, Rinneu Elias; Santos, Lia Raquel de Souza; Benvindo-Souza, Marcelino; Modesto, Richelle Sousa; Assis, Rhayane Alves; de Oliveira, Classius [UNESP] (Springer Nature, 2019)
Many agricultural practices cause environmental degradation that affects the cellular integrity of anurans. In the present study, we provided in situ data of Dendropsophus minutus, Physalaemus cuvieri, and Scinax fuscovarius collected in soybean/corn and conservation units in the Brazilian Cerrado. The in situ data showed no significant variation in the micronucleus frequency between the sites, only the reniform cells had a higher rate for the agricultural environment. A combined analysis of all nuclear erythrocyte abnormalities (ENAs = nuclear buds, reniform nuclei, apoptotic cell, binucleated, and anucleated cells) was recorded higher frequencies in farmland. Overall, Scinax fuscovarius was considered the best potential bioindicator for soybean/corn plantations. Finally, we recommend expanding the micronucleus test for in situ studies to expand our understanding of the sensitivity of native anuran species and provide a more systematic assessment of the adverse effects of environmental pollutants on wildlife.